2015
DOI: 10.3390/ijerph121012543
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Dissociative Nanocontainer for Peptide Drug Delivery

Abstract: The potency, selectivity, and decreased side effects of bioactive peptides have propelled these agents to the forefront of pharmacological research. Peptides are especially promising for the treatment of neurological disorders and pain. However, delivery of peptide therapeutics often requires invasive techniques, which is a major obstacle to their widespread application. We have developed a tailored peptide drug delivery system in which the viral capsid of P22 bacteriophage is modified to serve as a tunable na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…VLPs are an emerging class of targeted delivery vehicles with the potential to overcome the limitations of other NPs . In recent years, several groups have shown that VLPs can pack and deliver therapeutic cargo such as chemotherapeutic drugs, siRNA, RNA aptamers, proteins, and peptides . However, there are still challenges when using VLPs.…”
Section: Using Vlps Overcomes the Limitations Of Current Np‐based Thementioning
confidence: 99%
“…VLPs are an emerging class of targeted delivery vehicles with the potential to overcome the limitations of other NPs . In recent years, several groups have shown that VLPs can pack and deliver therapeutic cargo such as chemotherapeutic drugs, siRNA, RNA aptamers, proteins, and peptides . However, there are still challenges when using VLPs.…”
Section: Using Vlps Overcomes the Limitations Of Current Np‐based Thementioning
confidence: 99%
“…Kelly et al developed ap eptide drug-delivery system using P22 bacteriophage,w hich was modified to serve as at unable nanocontainer fort he packaging and applied ring-opening metathesis polymerization (ROMP) reactiont ot rigger disassembly of the capsida nd release of bioactive peptides under physiological conditions. [60] Gd 3 + -based MR contrast agents have drawn strongi nterest in recent years. Site-selective initiation of atom-transfer radical Figure 6.…”
Section: Applicationsmentioning
confidence: 99%
“…By modifying the scaffold protein that templates the self-assembly of the P22 procapsid, an arbitrary gene product can be incorporated within the procapsid shell [ 197 , 198 ]. Among the proteins that have been successfully packaged within the procapsid are the fluorescent proteins EGFP, mCherry, and ziconotide [ 186 , 197 , 199 ].…”
Section: Venom Peptide Drug Deliverymentioning
confidence: 99%
“…This was the first demonstration of delivery of ziconotide across a BBB model using a nanoparticle delivery system, providing an alternative route to intrathecal injection, which has thus far been the only delivery method. The results of this proof-of-concept experiment are promising towards the development of a tunable VLP nanocontainer for the delivery of peptide therapeutics across the BBB [ 186 , 199 ].…”
Section: Venom Peptide Drug Deliverymentioning
confidence: 99%